Concrete brick properties incorporating EPS and POFA as replacement materials - Adnan, Suraya Hani; Mohd Yassin, Nurain Izzati; Shahidan, Shahiron; Osman, Mohamad Hairi; Ahmad Jeni, Mohamad Luthfi; Wan Jusoh, Wan Amizah; Jamellodin, Zalipah; Abdul Hamid, Noor Azlina; Ahmad, Faridahanim (Penerbit Akademia Baru, 2021)
The implementation of sustainable construction and green building becomes the main attention of construction industries in Malaysia as it has been introduced by the government in the Construction Industry Transformation Programme (2016-2020). Therefore, this study focuses on the development of sustainable concrete bricks containing Expanded Polystyrene (EPS) and Palm Oil Fuel Ash (POFA) as sand and cement substitute materials. The percentage of replacement is 20%, 30%, 40% and 50% for EPS and 5%, 10%, 15%, 20% and 25% for POFA. There are 30 different mix designs of brick have been produced and their properties have been identified. Hardened brick density, compressive strength, water absorption and initial rate of absorption are the brick properties identified in this study. Based on the experimental results, it was found that the hardened brick density and compressive strength of the brick decreased as the replacement percentage increased. On the other hand, the water absorption and initial rate of absorption of the brick decreased as the percentage of EPS increased and increased as the percentage of POFA increased. Based on the findings, it shows that EPS and POFA has significantly contributes to the reduction of brick density. Next, for the compressive strength all the bricks have satisfied the minimum strength requirement of non-load bearing brick. Finally, for water absorption and initial rate of absorption, it has been found that majority of the bricks have an acceptable value based on standard requirements for brick. This can be concluded that EPS and POFA could be potential substitute materials for the manufacture of sustainable bricks.